Implementation of the modified free inquiry (MFI) learning model and its influence on students’ analytical abilities - Dias Rizki; Setiyo Prajoko; Shefa Dwijayanti Ramadani (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Analytical ability is a crucial part of the HOTS thinking element. This ability needs to be optimally trained through the learning process. However, the use of inappropriate learning models can lead to suboptimal analytical abilities in students. The Modified Free Inquiry (MFI) learning model is one of the suitable learning models for training analytical abilities. This study aims to analyze the effect of applying the MFI model on students’ analytical abilities concerning the immune system material. This research is a type of quasi-experimental study with a pretest-posttest control group design. The research sample consisted of 72 students, comprising control and experimental classes selected through cluster random sampling technique. The analysis technique used was ANCOVA test with the help of SPSS 24. The research results showed significance value of ANCOVA is 0.000 (p<0.05), indicating that the MFI model has an influence on students' analytical skills. This is also reinforced by the descriptive analysis results showing that the implementation of the MFI syntax can provide a positive trend in each dimension of analytical ability compared to the control class. Thus, the MFI model has a significant effect on improving students' analytical skills. This research is expected to strengthen theoretical studies in the field of analytical skills. Additionally, this study is also hoped to serve as a reference for teachers in choosing the right learning model to optimize students' analytical abilities.Abstrak. Kemampuan analitis merupakan bagian krusial dari elemen berpikir HOTS. Kemampuan ini perlu dilatih secara optimal melalui proses pembelajaran. Akan tetapi, penggunaan model pembelajaran yang kurang tepat dapat menyebabkan tidak optimalnya kemampuan analitis siwa. Model pembelajaran Modified Free Inquiry (MFI) merupakan salah satu model pembelajaran yang cocok digunakan untuk melatih kemampuan analitis. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan model MFI terhadap kemampuan analitis siswa pada materi sistem imun. Penelitian ini merupakan jenis penelitian kuasi-eskperimen dengan pretest-posttest control group design. Sampel penelitian yang digunakan sebanyak 72 siswa, terdiri dari kelas kontrol dan eksperimen yang dipilih melalui teknik cluster random sampling.Teknik analisis yang digunakan berupa Uji ANCOVA dengan bantuan SPSS 24. Hasil penelitian menunjukkan nilai signifikansi ANCOVA 0.000 ( p < 0.05), sehingga model MFI memberikan pengaruh terhadap kemampuan analitis siwa. Hal ini juga diperkuat dari hasil analisis deskriptif yang menunjukkan bahwa implementasi sintaks MFI mampu memberikan tren positif terhadap tiap dimensi kemampuan analitis dibanding kelas kontrol. Dengan demikian, model MFI berpengaruh signifikan terhadap peningkatan kemampuan analitis siswa. Adanya penelitian ini diharapkan dapat memperkuat kajian teoritis dalam bidang kemampuan analitis. Selain itu, penelitian ini juga diharapkan dapat menjadi referensi bagi guru dalam memilih model pembelajaran yang tepat guna mengoptimalkan kemampuan analitis siswa.